PENGAWETAN DUA JENIS KAYU MERANTI DENGAN METODE RENDAMAN - Barly Barly; Pipin Permadi (Pusat Penelitian dan Pengembangan Hasil Hutan, 1987)
This paper deals with an experiment of soaking treatment of two meranti wood species each with Wolmanit CB and Koppers Formula 7. In this process three groups of wood samples measure 50 cm x 5 cm x 5 cm were submerged in a bath of preservative for three, five and seven days. The treatability of the samples were studied. From this study the following conclusions could be drawn:Penetration of both preservatives could be increased into red meranti when high concentration were employed.Retention of Koppers Formula 7 increases on both meranti when high concentration was employed.In general the such treatment can not be recomended due to the result obtained is lower than the treatment spesification requirements for housing wood preservation.